In vitro inhibitory activity of IgY antibodies against Salmonella ser. newport isolated from horses - Bustos, Carla Paola (2021)
Equine salmonellosis is caused by several Salmonella serotypes, including Salmonella Newport, which cause enterocolitis and diarrhea. Treatment usually includes the administration of antibiotics. However, since multidrug-resistant Salmonella is commonly detected, alternative options to control the pathogen are needed. One of these options is the use of specific egg yolk antibodies (IgY) for passive immunotherapy. Thus, the aim of our work was to produce IgY antibodies against an equine S. Newport strain and assess their in vitro inhibitory activity. To this end, laying hens were immunized with an inactivated S. Newport strain by using either Freund's or Montanide adjuvant and egg yolk extracts were obtained. The levels of specific IgY antibodies against Salmonella in sera and egg extracts were determined by dot-blot and microagglutination. Besides, the IgY extracts were characterized by total protein analysis, SDS-PAGE, Western Blot, and inhibition of bacterial motility. IgY extracts showed high purity (87.7 to 91.8 %), high microagglutination titers, and the ability to inhibit the motility of the bacterium. The results using Montanide were similar to those using the traditional Freund's adjuvant. Thus, Montanide may also be a good adjuvant to produce IgY. IgY-technology represents a potential tool for the control of salmonellosis in horses.